2021
DOI: 10.34172/jlms.2021.77
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Enzyme-Catalyzed Crosslinkable Hydrogel as a Wound Dressing in Skin Tissue Engineering

Abstract: Introduction: Wound healing can have a very important impact on the patients’ quality of life. For its treatment, wound dressings have vital and effective uses. Indeed, the use of a proper wound dressing can improve the healing process and duration. Recently, wound dressings with unique properties have been prepared using natural hydrogels. In addition to the general wound characteristics, new generations of wound dressings, such as those lasting longer on the wound, can have specific properties such as transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Biocompatibility is the basis of tissue regeneration. Previous studies have proven the biocompatibility , of TG-Gel hydrogels and seeded human umbilical vein endothelial cells, human adipose-derived stem cells, , human fibroblast cells, human myoblasts cells as well as mouse mesenchymal stromal cells onto such similar materials or tried to encapsulate cells in the hydrogels. Similarly, our results showed that hPDLSCs could successfully attach to hydrogel surfaces and realize infiltrative growth into the hydrogels. We found that the group 40-5 showed almost exclusively the highest values in initial adhesion, cell proliferation, and cell viability.…”
Section: Discussionsupporting
confidence: 64%
“…Biocompatibility is the basis of tissue regeneration. Previous studies have proven the biocompatibility , of TG-Gel hydrogels and seeded human umbilical vein endothelial cells, human adipose-derived stem cells, , human fibroblast cells, human myoblasts cells as well as mouse mesenchymal stromal cells onto such similar materials or tried to encapsulate cells in the hydrogels. Similarly, our results showed that hPDLSCs could successfully attach to hydrogel surfaces and realize infiltrative growth into the hydrogels. We found that the group 40-5 showed almost exclusively the highest values in initial adhesion, cell proliferation, and cell viability.…”
Section: Discussionsupporting
confidence: 64%